2013
DOI: 10.1021/bm400694r
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar Structure of Methylcellulose Hydrogels

Abstract: It is well established that aqueous solutions of methylcellulose (MC) can form hydrogels on heating, with the rheological gel point closely correlated to the appearance of optical turbidity. However, the detailed gelation mechanism and the resulting gel structure remain poorly understood. Herein the fibrillar structure of aqueous MC gels was precisely quantified with a powerful combination of (real space) cryogenic transmission electron microscopy (cryo-TEM) and (reciprocal space) small-angle neutron scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
144
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(168 citation statements)
references
References 29 publications
17
144
3
Order By: Relevance
“…29 The mechanism of gel formation is based on the extent of hydrophobic interaction among MC chains that associate to form a fibrilar gel. 30 As temperature increases, hydrophobic interactions strengthen and chains are able to assemble and form the gel.…”
Section: Figure X2 Around Here X4 Structuring Using Polysaccharidesmentioning
confidence: 99%
“…29 The mechanism of gel formation is based on the extent of hydrophobic interaction among MC chains that associate to form a fibrilar gel. 30 As temperature increases, hydrophobic interactions strengthen and chains are able to assemble and form the gel.…”
Section: Figure X2 Around Here X4 Structuring Using Polysaccharidesmentioning
confidence: 99%
“…[19][20][21] The gelation process is attributed to an initial association of the hydrophobic methylated regions, followed by formation of a turbid gel and phase separation. 20,[22][23][24][25] The heat setting nature of MC, along with its thermoreversibility, 26 makes it appealing for use in cooking as a thickener or a binder. 18 Previous studies have shown that MC-agar solutions have much quicker gelation times compared to MC alone when held at a constant temperature.…”
mentioning
confidence: 99%
“…The same group of researchers has also demonstrated by cryogenic transmission electron microscopy and small-angle neutron scattering that MC hydrogels have a heterogeneous fibrillar structure that is responsible for their turbidity [66,67].…”
Section: Colloidal Dissolution and Gelation As Processes Involved In mentioning
confidence: 97%